Clinical Pathogen Stenotrophomonas maltophilia: Role of Flagella in Immunostimulation of Respiratory Tract and Possibility of Using as an Adjuvant (World Journal of Experimental Biosciences, 2021)
Finding a safe and cheap immune stimulant is one of the most important challenges facing immunologists working in vaccine production. The other challenge is finding a way to improve the immune response of people who suffer from an immune suppressive phenomenon. Stenotrophomonas maltophilia is considered one of the controversial pathogens because it is an opportunistic bacterium, but its infection rate increases over time. In the current study, the most important studies that dealt with pathological and immunological perspectives of S. maltophilia will be reviewed. Furthermore, it sheds light on flagella protein (flagellin) and its role in stimulating the innate immune response as well as the safe pro-inflammatory immune response. The current study showed that the flagella of S. maltophilia has the ability to stimulate the innate immune response, as well as the pro-inflammatory immune response, through binding to the toll-like receptor (TLR) 5 receptor, which in turn stimulates internal cellular interactions that result in the cells secreting immune mediators, including pro-inflammatory cytokines and chemokine. As well as activating various immune cells, especially phagocytic cells in the respiratory system, and increasing neutrophil infiltration to the mucosal layer of the respiratory tract system, which in turn increases the host response to other external pathogens. Studies have shown that administrating flagellin protein will stimulate the mucosal immune response in the respiratory system and help the host resist infectious diseases. These results pave the way for a belief that confirms the possibility of using this protein as an adjuvant in the future after conducting many in vivo experiments related to the evaluation toxicity of flagellin.